Transport Systems Tracking and Inventory Security: A Case of Mega Bakery, Kabale. - Ntaribi, Elijah (Kabale University, 2025)
The study was about Transport Systems Tracking and inventory Security: A case of Mega Bakery, Kabale and it was guided by the following study objectives; to assess the current state of transportation systems tracking technologies used by Mega bakery, Kabale, to identify the key security challenges faced by inventory Mega bakery, Kabale, and to evaluate existing policies and regulations related to cargo security in Mega Bakery, Kabale. The cross-sectional survey design was used to collect quantitative approach of research. This helped the researcher to collect in-depth data regarding the research study. Using Krejcie and Morgan table, the sample size was 66 respondents who were chosen purposively due to scarcity of resources available to the researcher. Simple random sampling that was employed to select respondents in order to reduce bias in sampling. Purposive sampling was used to select respondent’s categories who included management staff. Both qualitative and quantitative analysis tools were used by the researcher. Qualitatively, findings from the study were categorized into themes and sub themes. Field findings was coded together to generate frequencies and tallies. This was fed into computer using excel and word package to analyze data. Quantitative data analysis tools were used such as micro soft word, excel and the data was presented by frequency tables and percentages in order to make the presentation easier for the readers to interpret. The findings revealed that Mega Bakery, Kabale GPS Tracking Systems where many bakeries have adopted Global Positioning System (GPS) technology to monitor the location of delivery vehicles in real-time. They revealed that this allows firms to optimize routes, reduce delivery times, and improve customer satisfaction. They revealed that Mega Bakery Kabale uses GPS tracking to ensure that its fresh bread reaches customers within a specific timeframe, thereby maintaining quality. This was represented by 30% of the respondents. The findings revealed that transport licensing regulations in Uganda require all vehicles used for commercial purposes—including those transporting baked goods—to be registered with relevant authorities such as the Ministry of Works and Transport. These regulations also mandate that drivers undergo training on safe handling practices for perishable goods. One of the respondent cited out example of mega bakery firm may need to provide proof of vehicle registration along with evidence that their drivers have completed training on food safety protocols before they can legally transport their products as represented by 21% of the respondents.